Comparison of TikTok, Instagram, and YouTube Utilization in Improving Students’ Digital Literacy - Dina, Tyas Ayu Farah; Khoiriyah, Sapna (Proceeding International Conference on Education, 2025)
The rapid development of digital technology has transformed education, particularly in the use of social media as a learning medium. TikTok, Instagram, and YouTube are now increasingly utilized not only for entertainment but also as educational tools. This study aims to analyze and compare the effectiveness of these three platforms in improving students’ digital literacy. The research employs a library research method with a descriptive qualitative approach, drawing data from journals, books, and academic repositories. The findings showed that each platform has distinct advantages, TikTok effectively delivers microlearning that fosters engagement, Instagram strengthens visual literacy and creativity through interactive features, and YouTube supports deeper comprehension and independent learning with comprehensive materials and structured navigation. Despite these potentials, challenges remain, such as information overload, uncurated content, and distractions from advertisements or entertainment. The study concludes that the optimal use of social media platforms depends on careful selection based on learning objectives and student characteristics, along with teacher guidance in curating credible content and fostering critical evaluation skills. These findings contribute both theoretically and practically by emphasizing the importance of integrating social media strategically and responsibly into pedagogy to foster students’ digital literacy in the 21st century.